Ask questions and get helpful answers.

Consider the implicit equation 2xy-1=(x+y+1)^2

a) Compute and solve for the derivative dy/dx as a function of x and y.

b) Find the equation of the tangent line to the graph of the above when y=-1.

For part a, I found the derivative being equal -(x+1)/(y+1) but how would I find the equation of the tangent line when not given both x and y?

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩
5 answers
  1. Maybe my derivative isn't correct in the first place? I used the quadratic formula to solve for x and got x being equal to -1 but when I plug that into the equation I get 0/0, which certainly means I'm doing something wrong. Any ideas?

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  2. Any ideas anyone? I need to have this turned in by tomorrow, any help is greatly appreciated

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  3. 2xy-1=(x+y+1)^2
    2y + 2xy' = 2(x+y+1)(1+y')
    2y + 2xy' = 2(x+y+1) + 2(x+y+1)y'
    y' (2x - 2(x+y+1)) = 2x+2
    y' = -(x+1)/(y+1)

    So, your derivative is ok.

    when y = -1, x = -1, so y' = 0/0

    so, what happens near (-1,-1)?
    If y = -1+h, x = -1+h+√(2h)
    so, y' = -(h+√(2h))/h
    as h->0, y' -> -1 -√(2/h)
    So, it looks like a vertical tangent.

    But it still bothers me. If we look back at the original equation,

    (x+y+1)^2 = 2xy-1
    x^2+y^2+1+2xy+2x+2y - 2xy+1 = 0
    x^2+2x+1 + y^2+2y+1 = 0
    (x+1)^2 + (y+1)^2 = 0

    The only point which satisfies this equation is (-1,-1)!

    So, there is no tangent line at all, since f(x,y) is a single point!

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  4. That is the second strange tangent line problem today. The first one was horizontal :)

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  5. I had that on the back of my head when I was doing this but thought that wouldn't be possible, thanks so much!

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Answer this Question

Similar Questions

  1. calculus

    let y=(x+sin(x))^2 f(x)=? g(x)=? (f o g)'=? compute the derivative using the chain rule

  2. Calc

    g'(x)=tan(2/1+x^2) Let g be the function with first derivative given above and g(1)=5. If f is the function defined by f(x)=ln(g(x)), what is the value of f'(1)? I know the answer is 0.311, but I need steps as to why. Please and thanks.

  3. Calculus

    The line that is normal to the curve x^2=2xy-3y^2=0 at(1,1) intersects the curve at what other point? Please help. Thanks in advance. We have x2=2xy - 3y2 = 0 Are there supposed to be 2 equal signs in this expression or is it x2 + 2xy - 3y2 = 0 ? I'll

  4. Calc AB

    Remember that f(x) must be one-to-one (only one y-value for each x-value) over the domain where f –1(x)is defined as a function. So, in some cases you must restrict the domain of f(x) so that it's one-to-one. There might be more than one section of

  5. Calc AB

    Suppose that y = f(x) = x^2-4x+4 Then on any interval where the inverse function y = f^–1(x) exists, the derivative of y = f^–1(x) with respect to x is: a) 1/(2x-4) b) 1/(2y-4), where x and y satisfy the equation y=x^2-4x+4 c)(1/2)x^(-1/2)

  6. Math(Urgent)

    Compute the maximum product for two positive numbers x and y with the property that the sum of the first plus five times the second is 5000. 1) Indicate the objective equation 2) Indicate the constraint equation So the objective = f(x)=xy and the

  7. Math (Calculus) (mean value theorem emergency)

    Consider the graph of the function f(x)=x^2-x-12 a) Find the equation of the secant line joining the points (-2,-6) and (4,0). I got the equation of the secant line to be y=x-4 b) Use the Mean Value Theorem to determine a point c in the interval (-2,4)

  8. Calculus

    A rectangle is bounded by the x-axis and the semicircle y = sqrt(36-x^2). What length and width should the rectangle have so that its area is a maximum? I understand that 2xy = A and that 4x + 2y = P, but I'm not sure how to solve for a variable to plug

  9. Calculus

    Suppose the derivative of a function f is f′(x)=(x−8)^7(x−1)^4(x+19)^8. Then the function f is increasing on the interval what?

  10. calculus

    Suppose f is a one-to-one, differentiable function and its inverse function f^−1 is also differentiable. One can show, using implicit differentiation (do it!), that (f^−1)′(x)=1 / f′(f^−1(x)) Find (f^−1)′(−6) if f(−1)=−6 and

Still need help?

You can ask a new question or browse existing questions.